2012
DOI: 10.1016/j.jcf.2011.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and survival in cystic fibrosis patients after lung transplantation

Abstract: One- and five-year survival rates after LTx tend to be better in CF recipients with DM compared to those without DM. No impact of DM on the development of BOS was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 27 publications
6
28
1
1
Order By: Relevance
“…Both the study of Bradbury and co-workers and our study are based on a limited number of patients, but nevertheless show similar results. However, Hofer et al recently showed a positive impact of diabetes on survival, although this outcome surprised even themselves [13]. In contrast to our study, a considerable percentage of children was included and the era of performing transplantation started earlier (already in 1992), with a shorter time on the waiting list than our patients, especially in the group with diabetes (P = 0.008).…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Both the study of Bradbury and co-workers and our study are based on a limited number of patients, but nevertheless show similar results. However, Hofer et al recently showed a positive impact of diabetes on survival, although this outcome surprised even themselves [13]. In contrast to our study, a considerable percentage of children was included and the era of performing transplantation started earlier (already in 1992), with a shorter time on the waiting list than our patients, especially in the group with diabetes (P = 0.008).…”
Section: Discussioncontrasting
confidence: 91%
“…Gender was not a significant determinant for survival and the number of patients colonized with Burkholderia cenocepacia was too small to show the expected negative effect on survival [11]. However, Hofer et al recently showed a positive impact of diabetes on survival, although this outcome surprised even themselves [13]. We hypothesize that this higher rate of post-operative bleeding may possibly be attributed to lungs more firmly attached to the thoracic wall in patients with diabetes, possibly because of a higher rate of pre-transplant pulmonary infections.…”
Section: Discussionmentioning
confidence: 99%
“…8 Several factors, such as sex, malnutrition, and CF-related diabetes (CFRD), have been shown to have a negative impact on health outcomes in the general CF population [9][10][11][12][13][14][15] ; however, their effects on the post-transplant population are unclear. For example, depending on the study, investigators found that individuals with CFRD have better survival posttransplant, 16,17 found that individuals with CFRD have an increased risk of death after lung transplant, 8 or found no association with post-transplant survival. 7 Furthermore, female sex and the presence of malnutrition have been shown to have a negative impact on overall CF survival, but it is uncertain if these are important predictors in the posttransplant patient population.…”
mentioning
confidence: 99%
“…They proposed that the improvement of insulin sensitivity was related to the reduction in systemic inflammation related to chronic pulmonary infection . In some studies, pre‐existing CFRD or development after LT did not appear to be associated with worse outcomes; Hofer et al even found a trend toward better survival after LT in patients with CFRD. However, in several studies, the mortality in patients with CF appears higher among those with CFRD diagnosed before LT compared to those without .…”
Section: Cf‐related Diabetesmentioning
confidence: 99%